2011
DOI: 10.1016/j.stem.2011.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Direct Lineage Conversion of Terminally Differentiated Hepatocytes to Functional Neurons

Abstract: Summary Several recent studies showed that mouse and human fibroblasts can be directly reprogrammed to induced neuronal (iN) cells, bypassing a pluripotent intermediate state. However, fibroblasts represent heterogeneous mesenchymal progenitor cells that potentially contain neural crest lineages, and the cell of origin remained undefined. This raises the fundamental question whether lineage reprogramming is possible between cell types derived from different germ layers. Here, we demonstrate that terminally dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
219
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 320 publications
(233 citation statements)
references
References 25 publications
11
219
0
3
Order By: Relevance
“…In addition, although both adult and fetal neural stem cells in theory are able to be amplified using mitogens such as FGF2 or EGF, these neural stem cells always undergo undesired differentiation and tend to lose their potential to generate the appropriate type of cells for cell replacement therapy (Wright et al, 2006). Functional neurons (Vierbuchen et al, 2010;Ambasudhan et al, 2011;Marro et al, 2011;Pang et al, 2011;Qiang et al, 2011;Yoo et al, 2011), and lately subtype-specific neurons such as dopaminergic neurons (Caiazzo et al, 2011;Pfisterer et al, 2011) and motor neurons (Son et al, 2011) have been converted directly from other type of somatic cells of mouse and human by introducing pro-neuronal transcription factors or micro-RNA. The neurons generated through these procedures were called induced neurons (iNs) and the process was termed transdifferentiation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, although both adult and fetal neural stem cells in theory are able to be amplified using mitogens such as FGF2 or EGF, these neural stem cells always undergo undesired differentiation and tend to lose their potential to generate the appropriate type of cells for cell replacement therapy (Wright et al, 2006). Functional neurons (Vierbuchen et al, 2010;Ambasudhan et al, 2011;Marro et al, 2011;Pang et al, 2011;Qiang et al, 2011;Yoo et al, 2011), and lately subtype-specific neurons such as dopaminergic neurons (Caiazzo et al, 2011;Pfisterer et al, 2011) and motor neurons (Son et al, 2011) have been converted directly from other type of somatic cells of mouse and human by introducing pro-neuronal transcription factors or micro-RNA. The neurons generated through these procedures were called induced neurons (iNs) and the process was termed transdifferentiation.…”
Section: Introductionmentioning
confidence: 99%
“…This finding demonstrates that the same combination of neuronal transcription factors could activate the neuronal program and simultaneously silence the initial non-neuronal cell transcriptional program (Vierbuchen et al, 2010;Marro et al, 2011;Yang et al, 2011) and that the same transcription factors could produce similar induced neuronal cells from different cell types. However, although the initial transcriptional profile was silenced and neuronal profile acquired, these iN cells do possess some epigenetic memories of their cells of origin .…”
Section: Direct Reprogramming Of Non-neural Cells To Neuronsmentioning
confidence: 70%
“…Son et al reported that the ectopic expression of seven transcription factors (Ascl1, Brn2, Myt1 l, Lhx3, Hb9, Isl1 and Ngn2) could induce mouse and human fibroblasts to become motor neurons (Son et al, 2011). Marro et al (2011) reported the direct reprogramming of definitive endodermal cells (mouse hepatocytes) to induced neuronal cells with the same ABM factors, indicating that lineage conversion through forced expression of transcription factors is possible in any cell type.…”
Section: Direct Reprogramming Of Non-neural Cells To Neuronsmentioning
confidence: 99%
“…Moreover, the genetic lineage tracing system employed in this study allowed us to carefully investigate the expression of the donor cell transcriptome. Based on bulk and single-cell RNA expression studies, we concluded that the hepatocyte-specific transcriptional programme is robustly silenced in iN cells [27]. A more recent survey of various reprogrammed cell populations with the aspiration to measure the authenticity of target cell types came to the conclusion that the degree of transcriptional similarity to target cell types varies between different reprogrammed cells, which is mostly driven by non-proper silencing of the donor cell programmes highlighting the importance of transcriptional repression in reprogramming [28].…”
Section: Induced Neuronal Cells: Direct Lineage Conversion Between DImentioning
confidence: 99%